1997
DOI: 10.1002/(sici)1097-0215(19970703)72:1<102::aid-ijc15>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Egr‐1 expression in human, mouse and rat mammary cells and tissues correlates with tumor formation

Abstract: We have examined several types of tumor cell lines and shown that they invariably expressed little or no Egr-1, in contrast to their normal counterparts. We have previously shown that the expression of exogenous Egr-1 in human breast and other tumor cells markedly reduces transformed growth and tumorigenicity. We therefore hypothesized that the loss of Egr-1 expression plays a role in transformation. All human and mouse breast cancer cell lines and tumors examined had reduced Egr-1 expression compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 12 publications
6
89
0
Order By: Relevance
“…24 RT-PCR experiments performed on human thyroid tumors showed that the absence of Egr1 mRNA is always paralleled by the absence of PTEN mRNA, suggesting that Egr1-dependent mechanisms may play a role in the absence of PTEN gene expression that occurs during thyroid cell transformation. 24 Egr1 protein levels are suppressed or absent in a variety of human tumor cell lines 13,28 and tumors, including breast carcinoma, 28 glioblastoma, 14,15 lung cancer, 29,30 and lymphoma. 31 Moreover, in the case of human nonsmall-cell lung cancer, Ferraro et al 32 examined an extensive series of samples from over 125 patients and observed that Egr1 expression predicts both PTEN level and survival to a high degree of significance.…”
Section: Ptenmentioning
confidence: 99%
See 1 more Smart Citation
“…24 RT-PCR experiments performed on human thyroid tumors showed that the absence of Egr1 mRNA is always paralleled by the absence of PTEN mRNA, suggesting that Egr1-dependent mechanisms may play a role in the absence of PTEN gene expression that occurs during thyroid cell transformation. 24 Egr1 protein levels are suppressed or absent in a variety of human tumor cell lines 13,28 and tumors, including breast carcinoma, 28 glioblastoma, 14,15 lung cancer, 29,30 and lymphoma. 31 Moreover, in the case of human nonsmall-cell lung cancer, Ferraro et al 32 examined an extensive series of samples from over 125 patients and observed that Egr1 expression predicts both PTEN level and survival to a high degree of significance.…”
Section: Ptenmentioning
confidence: 99%
“…14 The observations indicate that Egr1 expression is commonly suppressed in tumors as has been observed in cells lines. 13,28 Paradoxically, increased expression of Egr1 is consistently observed in prostate cancer where growing evidence indicates that Egr1 is oncogenic. Russell and co-workers 55 observed that Egr1 mRNA levels were elevated in 12 of 12 cases of organ-confined prostate cancer but not in breast or ovarian cancers, or in rapidly dividing rat ventral prostate cells.…”
Section: Egr1-induced Oncogenesis Of Prostate Cancermentioning
confidence: 99%
“…S1P 1 receptor signaling negatively controls cell proliferation either by knockdown or by overexpression of the S1P 1 receptor in glioma cell lines. Furthermore, expression of the S1P 1 receptor correlated with that of early growth response-1 (Egr-1), which is an essential transcriptional factor considered to be a central regulator in tumor cell proliferation [20][21][22][23][24] through phosphatase and tensin homologue deleted in chromosome 10 (PTEN) in glioblastoma. These results suggest that S1P 1 receptor signaling plays an important role in the malignant behavior of human glioma.…”
mentioning
confidence: 99%
“…A number of reports indicate that EGR-1 acts as a tumor suppressor gene. EGR-1 is downregulated in tumors and an array of tumor cell lines 36 and is induced by several tumor suppressor proteins. 82,85 We also have identified EGR-1 as another NSAID-induced gene.…”
Section: Early Growth Response-1 (Egr-1)mentioning
confidence: 99%